2020
DOI: 10.2196/20840
|View full text |Cite
|
Sign up to set email alerts
|

Use of Patient-Reported Symptoms from an Online Symptom Tracking Tool for Dementia Severity Staging: Development and Validation of a Machine Learning Approach

Abstract: Background SymptomGuide Dementia (DGI Clinical Inc) is a publicly available online symptom tracking tool to support caregivers of persons living with dementia. The value of such data are enhanced when the specific dementia stage is identified. Objective We aimed to develop a supervised machine learning algorithm to classify dementia stages based on tracked symptoms. Methods We employed clinical data from 717… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
(79 reference statements)
1
9
0
Order By: Relevance
“…Furthermore, as the myGoalNav is not a checklist of symptoms, the tracking frequencies presented here are distinct from symptom prevalence . There are also limitations in the development of the staging algorithm model, such as potential bias in the training data because of clinician facilitation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, as the myGoalNav is not a checklist of symptoms, the tracking frequencies presented here are distinct from symptom prevalence . There are also limitations in the development of the staging algorithm model, such as potential bias in the training data because of clinician facilitation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, we developed an artificial neural network model to stage dementia, which was trained on data from 320 memory clinic patients [ 42 ]. That model was updated in 2020 using a support vector machine–supervised learning algorithm trained on 717 patients [ 44 ]. Data from these patients were captured with myGoalNav in a memory clinic, a long-term care study [ 45 ], and a dementia clinical trial [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vizcarra et al [ 112 ] validated previously published ML algorithms using convolutional neural networks (CNNs) and to determine if pathological heterogeneity may alter algorithm-derived measures using 40 cases from the Goizueta Emory Alzheimer's Disease Center brain bank, which displays an array of pathological diagnoses (including AD with and without Lewy body disease (LBD) and/or TDP-43-positive inclusions) and evaluated their levels of Aβ pathologies. Shehzad et al [ 113 ] used individualized symptom profiles from the pooled data (clinical data from 717 people from three sources: (1) a memory clinic, (2) long-term care, and (3) an open-label trial of donepezil in vascular and mixed dementia) to train various ML models to predict dementia severity (MCI, mild dementia, moderate dementia, or severe dementia). Tsao et al [ 114 ] combined a predictive multi-task ML method (cFSGL) with a novel ML-based multivariate morphometric surface map of the hippocampus (mTBM) to predict future cognitive scores (Alzheimer's Disease Assessment Scale cognitive scores 6, 12, 24, 36, and 48 months from baseline) of patients.…”
Section: Tasks In Ad Researchmentioning
confidence: 99%
“…Recent studies had shown that machine learning (ML) exhibited excellent performance in identifying MCI and dementia [11][12][13][14][15][16][17], but these mostly used biomarker data such as neuroimaging and CSF components that were expensive technologies [12,13,16]. ML diagnostic models based on cognitive data were gradually being applied [11,15,18,19].…”
Section: Introductionmentioning
confidence: 99%